Between the city and the farm: food environments in artisanal mining communities in Upper Guinea. Issue 2 (12th February 2022) - Nordhagen, Stella; Fofana, Mohamed L; Barry, Alpha O; Diallo, Sadio; Songbono, Joseph L; Stokes-Walters, Ronald; Zhang, Laetitia X; Klemm, Rolf; Winch, Peter J
Abstract: Objective: Artisanal and small-scale mining (ASM) is a widespread livelihood in low- and middle-income countries; however, many in ASM communities face high levels of poverty and malnutrition. The food environments in ASM communities have non-agricultural rural characteristics that differ from those in urban and agricultural rural areas examined in much existing food environment literature. Design: We examine these complex external and personal food environments in ASM communities via a study using qualitative and quantitative methods. Market surveys and a cross-sectional household survey, plus qualitative mining site non-participant observations and in-depth structured interviews, were conducted in three waves. Setting: Eighteen study sites in ASM communities in northern Guinea. Participants: Surveys covered mothers in mining households with young children ( n 613); in-depth interviews engaged caregivers of young children ( n 45), food vendors ( n 40) and young single miners ( n 15); observations focused on mothers of young children ( n 25). Results: The external food environment in these ASM communities combines widespread availability of commercially processed and staple-heavy foods with lower availability and higher prices for more nutritious, non-staple foods. Within the personal food environment, miners are constrained in their food choices by considerable variability in daily cash income and limited time for acquisition and preparation. Conclusions: We demonstrate that ASM communities have characteristics of both urban and rural populations and argue for greater nuance and appreciation of complexity in food environment research and resultant policy and programming.